Spatiotemporal Evolution and Driving Mechanism of NEP in Qilian Mountain National Park - Jiao, Jinfei (International Journal of Natural Resources and Environmental Studies, 2026)
Taking Qilian Mountain National Park as the study area, this research systematically analyzed the spatiotemporal evolution characteristics and driving mechanisms of carbon sources/sinks in the park based on the MOD17A3HGF net primary productivity (NPP) dataset and meteorological data including temperature, precipitation, humidity, and sunshine duration from 2000 to 2022. The methods applied included a net ecosystem productivity (NEP) estimation model, pixel-wise linear regression, and correlation analysis. The results showed that: From 2000 to 2022, the park’s NEP exhibited a fluctuating upward trend with a slope of 1.89 gCm2a, reaching a peak of 181.6 gCm2a in 2019. The region was dominated by carbon sinks overall, with carbon source areas accounting for less than 0.5% and showing a decreasing trend. Spatially, NEP was higher in the southeast and lower in the northwest. High-value areas were concentrated in the Eastern Qilian Mountains spruce forest–alpine meadow and Hexi Corridor arid desert–oasis agricultural ecological subzones, while low-value areas were distributed in the Qaidam Basin desert, Western Qilian Mountains alpine desert steppe, and Qinghai Lake Wetland alpine meadow subzone. NEP showed an increasing trend across all five ecological subzones, with growth rates ranked as: Hexi Corridor (3.88) > Eastern Qilian Mountains (2.31) > Western Qilian Mountains (1.3) > Qaidam Basin (1.02) > Qinghai Lake Wetland (0.25). An increasing NEP trend occurred in 98.8% of the park area, among which 73.4% showed an extremely significant increase. NEP was positively correlated with meteorological factors; temperature was the primary driving factor, followed by precipitation and humidity, while sunshine duration had a relatively weak effect. This study can provide a scientific basis for ecological conservation, restoration, and carbon sink enhancement in Qilian Mountain National Park.